What is schizophrenia: A neurodevelopmental or neurodegenerative disorder or a combination of both? A critical analysis - Gupta, Swapnil (Medknow Publications, 2010)
The etiology of schizophrenia has been the focus of intensive research for a long time. Perspectives have changed drastically with the development of new investigative techniques. Clinical observations made by Kraepelin, Clouston, Bender, and Watt are now being complemented by neuroimaging and genetic studies to prove the neurodevelopmental hypothesis. At the same time, neuropathological and longitudinal studies of schizophrenia often support a neurodegenerative hypothesis. To provide a theoretical basis to the available evidence, another hypothesis called the progressive neurodevelopmental model has also emerged. This review presents some key evidence supporting each of these theories followed by a critical analysis of each.